Apresiasi Sastra Indonesia di Sekolah - Maman S Mahayana (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
The essence of literary learning is appreciation, and that only can be realized if teacher and student read those literary works. Thereâ€™s numerous literary works around the world, especially traditional literary works like legends and folktales. Why those literary treasures have been abandoned by literary learning at school? Therefore, teachers must show their faith and bravery to deliver learning matters that they feel good, appropriate, and joyful. In curriculum, KTSP (unit-learning curriculum) have give freedom to translate the Standard of competence and Basic Competence. Thereâ€™s local content and matters that appropriate with local social-cultural condition?Â